The Effect of Advertising Attractiveness, Influencer Marketing, Online Customer Reviews on Brand Image and Purchase Decision: - - Yuliana Qofifah; Rojuaniah (PT Inovasi Pratama Internasional, 2025)
Advances in digital technology have changed the way companies interact with consumers, including in marketing communication strategies. In the context of the highly competitive telecommunications industry, the use of digital media is one of the keys to building brand image and influencing consumer purchasing decisions. This study was conducted to specifically analyze purchase decisions as a key variable influenced by various digital marketing communication factors, namely advertising attractiveness, influencer marketing, and online customer reviews, which then shape brand image. The purpose of this study was to more specifically measure the influence of advertising attractiveness, influencer marketing, and online customer reviews on brand image, as well as their impact on purchase decisions among Telkomsel product consumers in Wonosobo Regency. This type of research is quantitative with a purposive sampling technique distributed through questionnaires to 125 respondents. Primary data analysis was conducted using the Structural Equation Modeling (SEM) method. The results show that the independent variables of advertising attractiveness, influencer marketing, and online customer reviews significantly influence brand image, which in turn has a positive impact on purchase decisions. These findings provide important managerial implications for Telkomsel to continue optimizing digital-based marketing communication strategies, maintaining brand image consistency, and fostering customer engagement through social media. However, this study has limitations in terms of geographic coverage, focusing only on the Wonosobo region and being cross-sectional, thus not reflecting the dynamics of consumer perceptions over time. Further research is recommended to expand the study area and use a longitudinal approach to gain a deeper understanding and broader generalization of the results.